Genetic factors in isolated and syndromic laryngeal cleft. (February 2020) - Li, Youjin; Rui, Xiaoqing; Li, Niu
Abstract: A laryngotracheoesophageal cleft (LC) is a rare congenital anomaly of the upper aerodigestive tract resulting from the absence of fusion of the posterior cricoid lamina, which affects an abnormal communication between the larynx, trachea and esophagus. The genetic etiology of LC remains elusive. The involvement of genetic factors in the development of LC is suggested by reports of familial occurrence, and the increased prevalence of component features among first-degree relatives of affected individuals and murine knockout models. No consistent pattern of inheritance has been found in nonsyndromic patients, except for cases associated with described syndromes. Once the syndrome related to the laryngeal cleft is considered, an active search for the cleft must be initiated. The genetic evaluation of patients with LCs should be guided by the type and location of the malformation, specific medical history and a detailed physical examination. The application of genetic approaches, such as microarrays and exome sequencing might lead to elucidating the etiology of LCs.